Oral Care and Positioning to Prevent Ventilator-Associated Pneumonia: A Systematic Review - Eslam Bani Mohammad RN, MSN, PhD; Amani A. Al Eleiwah RN, MSN, PhD; Banan T. Qurdahji RN, MSN, PhD; Ahmad Rayan PhD, RN; Jafar A. Alshraideh PhD, RN; Lourance A. Al Hadid PhD; Muna S. Al Kharabsheh RN, MSN; Heba N. Hudhud MSN, CNS, RN; Suad Jakalat RN,MSN,PhD (SAGE Publishing, 2024)
Introduction Ventilator-associated pneumonia (VAP) is one of the most common nosocomial infections in critical patients. The negative impacts of VAP on patient outcomes emphasize the importance of effective preventive measures such as oral care and patient positioning. The aim of this review was to investigate the impact of oral care and positioning on the prevention of VAP among patients in the intensive care unit. Methods This review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was performed. The methodological quality of included studies was appraised using Joanna Briggs Institute checklists. Results In total 13 studies were included, all of them were randomized controlled trials. Six out of nine studies about oral care have significant results on VAP incidence. Regarding the position, Patients positioned at a 45-degree were less likely to develop VAP than those positioned at a 30-degree and those in a supine position. Conclusion Although patients positioned at 45-degree angle were less likely to develop VAP than those at 30-degree, it is necessary to individualize this practice before recommending it, once there are some contraindications, such as neurocritical patients. Regarding oral care to prevent VAP, considering the current guidelines' recommendation not to use oral chlorexidine, further studies evaluating alternatives are needed.